KOMPETENSI PEDAGOGIS GURU PENDIDIKAN AGAMA ISALAM DALAM MELAKSANAKAN EVALUASI PEMBELAJARAN (STUDI KASUS PADA MTS. EMPAT LIMA ASSA’ADAH DAN MTS. AL-BASHOR SAMBENG LAMONGAN) - Fathurrahman Fathurrahman; Zainul Asyhari (LPPM Institut Agama Islam Al-Hikmah Tuban, 2021)
Abstract: This study examines the ability of Islamic religious education teachers toevaluate learning which is one of the indicators of teacher pedagogical competence inaddition to understanding the characteristics of students, understanding educationaltheory, the ability to develop curriculum and learning tools. Qualitative descriptiveapproach is used in this research, data collection is done by interview technique,participant observation, and documentation, then inductive analysis is carried out inorder to reveal and draw conclusions on the existing events. The results of the studyshow that 1) Good PAI MTs teachers. Four Five Assa'adah and PAI MTs teachers. Al-Bashor has an adequate understanding of the concept of assessment and evaluation oflearning. 2) Perform the procedure for assessing learning PAI subjects as stipulatedin the curriculum by conducting process assessments and assessments of learningoutcomes. 3) MTs PAI teacher. Four Five Assa'adah use the evaluation results morefor the improvement and development of learning, PAI MTs teachers. Al-Bashor usesinformation technology media more in the utilization of the evaluation results.Keyword: Pedagogical Competence, PAI Teacher, Learning Evaluation